A higher integrability theorem from a reverse weighted inequality. Issue 6 (17th October 2019) - Saker, Samir; O'Regan, Donal; Agarwal, Ravi
Abstract: In this paper, we establish some weighted Muckenhoupt‐ and Gehring‐type inequalities. These are obtained by employing new inequalities of Hardy type. We also present a higher integrability result.